Postdischarge Adverse Events Among Patients Who Received Home Health Care Services. Issue 4 (November 2019) - Tsilimingras, Dennis; Zhang, Liying; Chukmaitov, Askar
Adverse events that occur in urban and rural adults during the posthospitalization period have become a major public health concern. However, postdischarge adverse events for patients receiving home health care have been understudied. The objective of this study was to identify the prevalence and risk factors associated with postdischarge adverse events for patients who received home health care services. We analyzed data from a prospective cohort study that was conducted among patients who were hospitalized in the Tallahassee Memorial Hospital from December 2011 to October 2012. Telephone interviews were conducted by trained nurses who contacted patients within 4 weeks after discharge. Physicians reviewed cases with possible adverse events that were triaged by the nurses. The adverse events that were identified were categorized as preventable, ameliorable, and nonpreventable/nonameliorable. Nearly 39% of 85 patients who received home health care experienced postdischarge adverse events that were predominantly preventable or ameliorable. The associated risk factors were living alone (odds ratio [OR] = 7.860, p = .020), insured by Medicare or Medicaid (OR = 6.402, p = .048), type 2 diabetes mellitus (OR = 6.323, p = .004), pneumonia (OR = 5.504, p = .004), and other infections (OR = 4.618, p = .031). This study was able to identify that nearly one in every two patients who received home health care after hospital discharge experienced an adverse event. Patient safety research needs to focus in the home by developing specific interventions to avert adverse events and improve patient safety during the delivery of home health care services.